Potencial energético da co-digestão da biomassa de microalgas no tratamento de esgoto sanitário em reatores UASB - Azeredo, Ludimila Zotele (2016)
This study aims to estimate the energy potential of a new type of wastewater treatment plant, whose system was designed by the Núcleo Água team from UFES and aims maximizing the use of energy, nutrients and water for reuse. The association in series of preliminary treatment step, UASB reactor, high rate pond and a solid separation phase - liquid collection and recycling of microalgae, composes the treatment system. This microalgae biomass is sent to the UASB to maximize biogas production during anaerobic digestion and increase energy system availability. To quantify the Energy Availability (EID) by performing mass balance and energy individualized for each process and for the integrated system, mathematical models of design and experiments reported in the literature were used. The DIE estimated, in the form of biogas, was 6,78 W per person (0,99KWh / m3 ) in UASB reactor without digestion of biomass from post-treatment, and the integrated system, after the co-digestion of microalgae showed an EID of 10,21 W per person (1.75 KWh / m3 ). The results indicated a positive energy balance, being the system available energy (1.75 KWh / m3) is 13 (thirteen) times greater than the demand required for its operation (0.13 KWh / m3.d) and 03 (three) times the amount produced when converted into electrical energy. (0.50 KWh / m3). This new wastewater treatment plant model can be considered to have a positive balance of energy, featuring operational simplicity, operating in the tertiary treatment of sewage, allowing the recovery of nitrogen and phosphorus nutrients, operating in sequestering CO2 and hence contributing to reducing the concentration of green house gases in the atmosphere.